Founding Chair, Meet New Chair: Collaborating Through Chair Successions - James F. Konopack PhD; Christopher Hirschler PhD (Academic Chairpersons Conference Proceedings, 2017)
Challenges abound for new chairs, including the responsibility of [re]shaping the department’s vision. This can be doubly challenging when the founding chair moves into the dean’s office. In this session, founding chair and new chair share their story and facilitate discussion about a collaborative leadership transition.
Keywords: leadership; transition; collaboration; metacognition; consensus